Management Of The Tahfidz Al Qur'an Program In An Effort To Improve The Quality Of Islamic Education At Anak Sholeh Primary School, Hinai District - Ansyari, Rija; Mardianto, Mardianto; Daulay, Nurika Khalila (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
The purpose of this study is to examine how the tahfiz program is run at SDIT Anak Sholeh in Hinai District, Langkat Regency, with the goal of raising the standard of Islamic education. Data is gathered by observation, interviews, and documentation studies using a qualitative, descriptive methodology. Teachers who teach the Tahfiz of the Qur'an, as well as the head of the madrasa and the deputy head for curriculum, served as research subjects. According to the research findings, improving the quality of madrasas necessitates paying attention to the extracurricular activities of students, the performance of madrasa heads, and the availability of suitable facilities and infrastructure. governance over finances for instruction, scheduling, and buildings and infrastructure are additional essential tools for the madrasa head's effective governance. Madrasah quality assurance initiatives include supporting teacher career progression, raising graduation rates, and assessing education reports. In summary, this study highlights the importance of madrasa heads focusing on critical elements such extracurricular activities, teacher competency, facilities and infrastructure, and performance in order to improve the caliber of madrasas. Additionally essential to raising the caliber of Islamic education at SDIT Anak Sholeh are efficient control and quality assurance.